Therapeutic difficulties related to optimization of pemphigus vulgaris treatment - Leonik, Szymon; Karpińska, Emilia; Owsińska, Agnieszka; Sedlaczek, Katarzyna; Bergler-Czop, Beata (Dermatology Review/Przegląd Dermatologiczny, 2020)
A 60-year-old man with extensive erosive lesions within the scalp and face, limbs, trunk, and nasal and oral mucous membrane involvement was admitted to the ward with worsening of symptoms in the course of pemphigus vulgaris. The exacerbation took place during an attempt to reduce doses of immunosuppressive drugs and glucocorticosteroids. Additional examinations, otorhinolaryngological and dental consultation did not show another cause of this condition. Biological therapy with a monoclonal antibody directed against the CD20 antigen, rituximab, was introduced. The study presents the treatment efficacy in the patient 2 weeks after the last drug dose and compares them with the latest available knowledge on rituximab therapy in pemphigus vulgaris.